PENINGKATAN KETERAMPILAN MENULIS TEKS BIOGRAFI MELALUI METODE 5W+1H PADA SISWA KELAS X LP SMK CENDEKIA MADIUN - Winda Arini Tantya; Agung Nasrullah Saputro; Harning Diah Juni Astuti (STKIP Subang, 2026)
This study aimed to improve students' biography writing skills through the implementation of the 5W+1H method in Class X LP of SMK Cendekia Madiun in the 2025/2026 academic year. The study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model consisting of planning, action, observation, and reflection stages. The participants were seven students of Class X LP. Data were collected through observation, writing tests, documentation, and field notes. The data were analyzed using qualitative and quantitative descriptive techniques. The findings revealed that the implementation of the 5W+1H method improved students’ biography writing skills. The average score in the pre-cycle stage was 65.14 with a learning mastery percentage of 42.86%. In Cycle I, the average score increased to 72.14 with a mastery percentage of 57.14%. In Cycle II, the average score improved to 82.29 with a mastery percentage of 85.71%. The N-Gain score of 0.49 indicated a moderate level of improvement. In addition to improving learning outcomes, the 5W+1H method enhanced students’ participation in identifying, organizing, and developing information into systematic biography texts. Therefore, the implementation of the 5W+1H method proved effective in improving students' biography writing skills in Class X LP at SMK Cendekia Madiun.